Additive manufacturing of a functionally graded high entropy alloy using a hybrid powder-bed wire-based direct energy deposition approach - Lu, Yao; Wang, Jun; Williams, Stewart W.; Zhu, Lisong; Ding, Jialuo; Diao, Chenglei; Jiang, Zhengyi (Elsevier, 2023)
A functionally graded AlxCoCrFeNi high entropy alloy with a variation in Al concentration along the building direction was in-situ produced using a hybrid powder-bed wire-based direct energy deposition process. A continuous transition from a single FCC structure to a major BCC+minor FCC dual-phase structure was achieved, benefiting from the remelting and reheating process during the deposition. In the FCC→BCC transition zone, the dendritic core region is identified as an FCC matrix decorated by AlNi-rich ordered B2 precipitates. The interdendritic area shows B2 precipitating in the FeCr-rich disordered A2 matrix. Additionally, the interface between the two regions shows that the A2 phase and ordered Cr3Fe intermetallic phase precipitate at the B2 phase. The mechanical properties show a tendency for higher strength and hardening rate but lower plasticity corresponding to the areas with higher Al content. Through quantitative estimation of different strengthening mechanisms, the contribution from precipitation strengthening became increasingly apparent as Al content increased. Other strengthening modes, including solid solution and dislocations, also contribute to the total strength. This investigation realises a novel additive manufacturing method combining powder bed and wire feeding, which can produce a more convenient and cost-effective gradient material with a complex composition.
Keywords: Hybrid direct energy deposition; Functionally graded material; High entropy alloy; Microstructure evolution; Mechanical properties